Development of Mobile Application "My Equine First Aid-Traumatic Injuries" - Tu, Shen Jiang, 1994-, author 618131; Nurwina Akmal Anuar, 1985- 530198 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Sains (Pengurusan Ekuin)) - Universiti Teknologi Malaysia, 2018